Analisis Pengaruh Neraca Perdagangan, Suku Bunga dan Arus Modal Masuk terhadap Nilai Tukar Rupiah di Indonesia - Anis Nurul Laili; Diah Wahyuningsih (Universitas Jember, 2022)
The purpose of this study was to determine the effect of trade balance, interest rates and capital inflows on the rupiah exchange rate. The data used is time series data or time series in the form of years, namely from 1987 to 2019. This study uses a quantitative approach by using the error correction model (ECM) estimation method. The data analysis techniques used include: data stationarity test, cointegration test, estimation of short-term and long-term ECM, and classical assumption test. And the results obtained in this study are that in the long term the trade balance variable has a positive and significant effect on the rupiah exchange rate, interest rates have a positive and significant effect on the rupiah exchange rate. FDI has a positive and significant effect on the rupiah exchange rate and PFI has no effect on the rupiah exchange rate balance. While in the short term, the trade balance variable has a positive and significant effect on the rupiah exchange rate, interest rates have a positive and significant effect on the rupiah exchange rate, FDI has no significant effect on the rupiah exchange rate and FPI has no effect on the rupiah exchange rate. Keywords: Error Correction Model, Foreign Direct Investment, Portfolio Foreign Investment, Interest Rate, Exchange Rate, Trade Balance